EKSPLORASI DESAIN BUSANA KASUAL MUSLIM DENGAN MOTIF PUCUK REBUNG MELALUI APLIKASI SKETCHBOOK - Puspita Sari, Della; Ridwan Misbahudin, Agus (Jurnal Socia Akademika, 2025)
This research aims to explore the process of making a casual Muslim fashion design with pucuk rebung pattern using SketchBook application and analyse the design results from the aspects of aesthetics, function, innovation, trend suitability, and colour selection. The research method employed is a descriptive qualitative approach, utilising data collection techniques that include interviews with six expert sources and questionnaires administered to 30 respondents. The results showed that the design-making process was done systematically through concept determination, making moodboards, croquis, fashion sketches, colouring, and digital design refinement using a sketchbook. Based on the questionnaire results, the average category of Strongly Agree was 58% and Agree was 55.33%. The aesthetic aspect obtained the highest percentage of Strongly Agree at 66.67%, indicating that the design was considered visually appealing. The aspects of function, innovation, and trend suitability also received high scores, indicating that the design suits the needs of modern Muslim casual wear. However, innovation and colour selection still need to be improved to make the design more unique and optimal in the future. This research proves that the sketchbook application is effective in supporting the creation of traditional patterned Muslim casual fashion designs with a modern look that is relevant to current fashion trends.